PERANAN RELATIONAL BENEFITS DAN PERCEIVED VALUE DALAM MENINGKATKAN TRUST DAN LOYALITAS PELANGGAN KLINIK KECANTIKAN - Dexi Triadinda; Astrid Puspaningrum; Ananda Sabil Hussein (Jurnal Bisnis dan Manajemen, 2018)
This study analyzed the influence of relational benefits and perceived value in increasing customer trust and loyalty. This study used the data of 130 questionnaires with purposive sampling as the sampling method performed on Miracle Aesthetic beauty clinic in Malang. The population was all customers of Miracle Clinic who were currently in Miracle Clinic. The data analysis instrument was Structural Equation Modeling (SEM) on program SmartPLS version 2.0. The analysis result showed that relational benefits had the highest influence on trust and loyalty. Perceived value influenced the increase of customer trust and loyalty. In this study, trust also increased customer loyalty and increase the influence of relational benefits on loyalty and perceived value on loyalty partially. Loyal customer contributed to Miracle by performing indirect marketing through word of mouth. Then, customers made Miracle Clinic in Malang their main preference in beauty service. The managerial implication suggested by this study is emphasizing on the implementation of relational benefits and increasing perceived value of old and new customers so that the customers trust the company more and be loyal. DOI : https://doi.org/10.26905/jbm.v5i1.2317